Hybrid Injectable Sol-Gel Systems Based on Thermo-Sensitive Polyurethane Hydrogels Carrying pH-Sensitive Mesoporous Silica Nanoparticles for the Controlled and Triggered Release of Therapeutic Agents - Boffito, Monica; Torchio, Alessandro; Tonda-Turo, Chiara; Laurano, Rossella; Gisbert-Garzarán, Miguel; Berkmann, Julia C.; Cassino, Claudio; Manzano, Miguel; Duda, Georg N.; Vallet-Regí, María; Schmidt-Bleek, Katharina; Ciardelli, Gianluca (Frontiers in Bioengineering and Biotechnology, 2020)
Injectable therapeutic formulations locally releasing their cargo with tunable kinetics in response to external biochemical/physical cues are gaining interest in the scientific community, with the aim to overcome the cons of traditional administration routes. In this work, we proposed an alternative solution to this challenging goal by combining thermo-sensitive hydrogels based on custom-made amphiphilic poly(ether urethane)s (PEUs) and mesoporous silica nanoparticles coated with a self-immolative polymer sensitive to acid pH (MSN-CS-SIP). By exploiting PEU chemical versatility, Boc-protected amino groups were introduced as PEU building block (PEU-Boc), which were then subjected to a deprotection reaction to expose pendant primary amines along the polymer backbone (PEU-NH2, 3E18 -NH2/gPEU–NH2) with the aim to accelerate system response to external acid pH environment. Then, thermo-sensitive hydrogels were designed (15% w/v) showing fast gelation in physiological conditions (approximately 5 min), while no significant changes in gelation temperature and kinetics were induced by the Boc-deprotection. Conversely, free amines in PEU-NH2 effectively enhanced and accelerated acid pH transfer (pH 5) through hydrogel thickness (PEU-Boc and PEU-NH2 gels covered approximately 42 and 52% of the pH delta between their initial pH and the pH of the surrounding buffer within 30 min incubation, respectively). MSN-CS-SIP carrying a fluorescent cargo as model drug (MSN-CS-SIP-Ru) were then encapsulated within the hydrogels with no significant effects on their thermo-sensitivity. Injectability and in situ gelation at 37°C were demonstrated ex vivo through sub-cutaneous injection in rodents. Moreover, MSN-CS-SIP-Ru-loaded gels turned out to be detectable through the skin by IVIS imaging. Cargo acid pH-triggered delivery from PEU-Boc and PEU-NH2 gels was finally demonstrated through drug release tests in neutral and acid pH environments (in acid pH environment approximately 2-fold higher cargo release). Additionally, acid-triggered payload release from PEU-NH2 gels was significantly higher compared to PEU-Boc systems at 3 and 4 days incubation. The herein designed hybrid injectable formulations could thus represent a significant step forward in the development of multi-stimuli sensitive drug carriers. Indeed, being able to adapt their behavior in response to biochemical cues from the surrounding physio-pathological environment, these formulations can effectively trigger the release of their payload according to therapeutic needs.